Water quality and food safety: A review and discussion of risks - Jawahar, Puja; Ringler, Claudia (IWA Publishing, 2009)
While increased diversification of developing-country diets as a result of agricultural and economic growth has improved nutritional status and human health, the increased consumption of high-value products—particularly fresh fruits, vegetables, dairy and animal products—has lead to significant food safety risks associated with unsafe management and use of water resources These risks are both magnified and masked in developing countries due to a lack of regulation combined with a dearth of data and information on the relations between water use, water quality and food safety risks. Given the likely estimated rapid increase in production, trade, and consumption of agricultural commodities with high water-related food safety risks, avoiding contamination and maintaining water quality and food safety are becoming growing public health issues in developing countries. This paper introduces the linkages between water quality and food safety, describes the causes for declining water quality levels, and identifies the various stages of the production process that are vulnerable to contamination due to water use. It concludes with a review of constraints to food safety and water quality management and identifies the main research gaps relevant to agricultural water management in developing countries.